Maria Sebagai Model Ketaatan Menurut Luk.1:26-38 dan Lumen Gentium - Fransiskus Bhanu Viktorahadi (P3TK, Sanata Dharma University, 2021)
The current paper aims to highlight the unrestricted obedience expressed by Mary when declaring herself ‘the handmaid of the Lord’ and when demanding that the divine will would be accomplished in her, just when she agrees to be chosen by God as virginal mother of his divine Son incarnate. The elements of the unrestricted obedience are drawn out of the text Luke 1:26-38 using the Narrative Analysis Method. Apart from that, these elements were also sought and found by analyzing the Second Vatican Council’s Dogmatic Constitution ‘Lumen Gentium, especially the section on the Church’s view of Mary (53-69). Looking to Mary as an example, Christians learn to obey God in the path of faith and finds the values that lead him or her through the paths of the Christian life.